# Solve for y 8(y-1)-3y=6(2y-6)

8(y-1)-3y=6(2y-6)
Simplify 8(y-1)-3y.
Simplify each term.
Apply the distributive property.
8y+8⋅-1-3y=6(2y-6)
Multiply 8 by -1.
8y-8-3y=6(2y-6)
8y-8-3y=6(2y-6)
Subtract 3y from 8y.
5y-8=6(2y-6)
5y-8=6(2y-6)
Simplify 6(2y-6).
Apply the distributive property.
5y-8=6(2y)+6⋅-6
Multiply.
Multiply 2 by 6.
5y-8=12y+6⋅-6
Multiply 6 by -6.
5y-8=12y-36
5y-8=12y-36
5y-8=12y-36
Move all terms containing y to the left side of the equation.
Subtract 12y from both sides of the equation.
5y-8-12y=-36
Subtract 12y from 5y.
-7y-8=-36
-7y-8=-36
Move all terms not containing y to the right side of the equation.
Add 8 to both sides of the equation.
-7y=-36+8
Add -36 and 8.
-7y=-28
-7y=-28
Divide each term by -7 and simplify.
Divide each term in -7y=-28 by -7.
-7y-7=-28-7
Cancel the common factor of -7.
Cancel the common factor.
-7y-7=-28-7
Divide y by 1.
y=-28-7
y=-28-7
Divide -28 by -7.
y=4
y=4
Solve for y 8(y-1)-3y=6(2y-6)

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top